2020
DOI: 10.3390/en13123232
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Energy Performance of a Solar Low Energy House with Regard to Aspects of Energy Efficiency and Smartness of the House

Abstract: The paper shows how difficult it is to prove technically that a building really is both low energy and smart, and that all aspects of energy efficiency have been treated equally. Regulations connected to the determination of the energy performance of residential buildings take into account only space and hot water heating energy consumption and define the indices of maximal primary energy consumption, but not energy needs based on the architecture of the building. A single family house designed and constructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The findings of this research coincide with some in the current literature that adoption of improved technologies has positive impact on energy efficiency (Oikonomou et al, 2009;Mrówczyńska et al, 2018); initiatives on energy use has significant impact on energy efficiency (Chwieduk and Chwieduk 2020); construction and design positively drive energy efficiency (Chwieduk and Chwieduk 2020); appliances and equipment has positive effect on energy efficiency (Stagnitta et al, 2020) and management practices of firm positively drive energy efficiency (Boyd and Curtis, 2014;Martin et al, 2012;Bloom et al, 2010). Accordingly, results indicated that management practice plays the most important role for driving energy efficiency.…”
Section: Evaluation Of Structural Modelsupporting
confidence: 86%
See 2 more Smart Citations
“…The findings of this research coincide with some in the current literature that adoption of improved technologies has positive impact on energy efficiency (Oikonomou et al, 2009;Mrówczyńska et al, 2018); initiatives on energy use has significant impact on energy efficiency (Chwieduk and Chwieduk 2020); construction and design positively drive energy efficiency (Chwieduk and Chwieduk 2020); appliances and equipment has positive effect on energy efficiency (Stagnitta et al, 2020) and management practices of firm positively drive energy efficiency (Boyd and Curtis, 2014;Martin et al, 2012;Bloom et al, 2010). Accordingly, results indicated that management practice plays the most important role for driving energy efficiency.…”
Section: Evaluation Of Structural Modelsupporting
confidence: 86%
“…According to Chwieduk and Chwieduk (2020), design and construct of building are perceived as important for saving energy or use energy efficiently. The cleverness of the building's design and architecture demonstrates its ability to optimize the ambient surrounding to minimize energy demands for space heating or space cooling, simultaneously being able to utilize renewable energy and waste heat available to the building.…”
Section: Factors That Impact On Energy Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…The greatest amount of solar energy in Poland reaches the collector surface in June when the sky is cloudless, when the sun is at its highest point above the horizon (62.4°). In December, on the other hand, this energy is much lower because the Sun is at the lowest point (15.5°) (Global solar Atlas, 2020; NASA Solar Radiation, 2020; Chwieduk and Chwieduk, 2020;Zelazna et al, 2020;The World Bank, 2020). Summer months are characterized by the greatest number of hours of insolation; direct radiation may constitute 90% of the total radiation reaching the earth and thus reach 1,050 W/m 2 .…”
Section: Meteorological Possibilities Of Using Solar Collectors Installations In Polandmentioning
confidence: 99%
“…Heating and cooling energy consumption of a building results from thermal balance governing heat gains and losses [23] and may be lowered using solar energy. Recently, different methods to control solar energy flow in connection with a building's energy performance have been presented, such as windows with different thermal (U) and solar energy (g) transmittances [24,25], shading strategies [26], and inclination angles of windows [27].…”
Section: Literature Reviewmentioning
confidence: 99%